2020
DOI: 10.7567/1347-4065/ab6461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Si nanowire/nanosheet complexes from CaSi2 crystals by thermal annealing under MnCl2/NH4Cl vapors

Abstract: Si-based nanowire/nanosheet bundle complexes were synthesized from CaSi 2 crystal powders by thermal annealing under MnCl 2 /NH 4 Cl vapors. The formation of the complexes is a result of two processes that simultaneously occurred. One is the nanosheet bundle synthesis by Ca-atom extraction from the CaSi 2 crystals. Another is the growth of the Si nanowires by thermal annealing using MnCl 2 . The mixing of these materials resulted in the successful synthesis of the nanowire/nanosheet bundle complexes. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The density of the nucleation sites of the Si crystals by Ca atom extraction on the side wall of the CaSi 2 crystals increased with increasing thermal annealing temperatures, thereby leading to the formation of thinner nanosheets. 49) The morphology evaluation indicated that the thickness of MnSi 1.7 sheets is thinner than that of Mg 2 Si nanosheet bundles. 27) A small void space was formed between the nanosheets owing to the reduction in volume caused by the Ca atom extraction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The density of the nucleation sites of the Si crystals by Ca atom extraction on the side wall of the CaSi 2 crystals increased with increasing thermal annealing temperatures, thereby leading to the formation of thinner nanosheets. 49) The morphology evaluation indicated that the thickness of MnSi 1.7 sheets is thinner than that of Mg 2 Si nanosheet bundles. 27) A small void space was formed between the nanosheets owing to the reduction in volume caused by the Ca atom extraction.…”
Section: Discussionmentioning
confidence: 97%
“…In this case, MnCl 2 , MnSi 1.7 , or other Mnbased compounds acted as catalyst for the growth of Si nanowires when the excess Si atoms were supplied. 10,49,50) It is interesting to compare the results with and without NH 4 Cl source for the nanosheets synthesized at 600 °C for 10 h (Samples 5 and 6). When NH 4 Cl was used as the source material, the dissociation of NH 4 Cl provided HCl formation, similar to the case of using deliquescent chloride; the HCl molecules were significantly transported to the CaSi 2 crystals at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain mono or multilayered silicene or nanostructured Si by extracting the Ca from the CaSi 2 crystal, several chemical treatment methods have been adopted. [27][28][29][30] Recently, An et al claimed that a bulk CaSi 2 crystal could be transformed to polycrystalline Si while maintaining its morphology (outer shape of crystallites) after heating above 800 °C in a vacuum. 31) In comparison to those methods, as speculated from the results, the Ca extraction process (shown as Fig.…”
Section: Discussionmentioning
confidence: 99%